الاغتيال المعنوي للأفراد والمؤسسات بين الفقه الإسلامي والقانون الإندونيسي : دراسة تحليلية وتأصيلية - قادران، إمام سوجوكو (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study examines the judicial and legal meanings of character assassination and the criteria that measure the true definition of character assassination. The researcher adopted the inductive, comparative and analytical methods. The inductive method was used by the researcher in referring to the classic and contemporary writing in books, journals, articles, official websites, and interviews on the issue of character assassination. The comparative method was also employed in comparing between the Islamic jurisprudence and Indonesian law. In addition, the analytical method was used to collect, discuss and analyze the data such as texts, views of Islamic Jurisprudence and Indonesian law, interview with the committee of fatwa – at the Council of Indonesian Moslem Scholar. The results of the study showed that character assassination has criteria or measurements that must be completed; one is not guilty of charge when the measurement is absent. Character assassination is categorized under the crimes of Ta'zir which imposes different types of sanctions, ranging from the mildest to the most severe punishment like death sentence. The study found that the practice of character assassination is a phenomenon of public perception within society and could only be dealt with modern legal means rather than through Islamic Jurisprudence.